Decorating (C(60))(n)(+), n = 1–3, with CO(2) at low temperatures: Sterically enhanced physisorption() - Mauracher, A. (Int J Mass Spectrom, 2013)
Multiple attachment of CO(2) to the monomer, dimer and trimer cations of C(60) has been observed in the mass spectra of He nanodroplets sequentially doped with C(60) and CO(2) and exposed to electron ionization at 50 eV. Remarkable anomalies were seen in the ion yield for CO(2) coverage for (C(60))(2)(+)(CO(2))(8) and (C(60))(3)(+)(CO(2))(1,2). These provide insight into the influence of steric properties on the nature of physisorption. The enhanced stabilities of (C(60))(2)(+)(CO(2))(8) and (C(60))(3)(+)(CO(2))(1,2) are attributed to physisorption inside the “groove” of the dimer and the two “dimples” in the trimer cations of C(60). Molecular dynamics simulations provide a qualitative assessment of the observed physisorption and a useful visualization of structural aspects.